2010
DOI: 10.1021/om100971d
|View full text |Cite
|
Sign up to set email alerts
|

Living 3,4-Polymerization of Isoprene by Cationic Rare Earth Metal Alkyl Complexes Bearing Iminoamido Ligands

Abstract: in 65-85% isolated yields. X-ray analyses show these complexes have decreasing steric hindrance in the coordination spheres of the metal centers in the order 1 > 2 > 3 > 4 > 5 > 6. A mechanism involving intramolecular alkyl and hydrogen migration is supported on the basis of DFT calculations to account for ligand alkylation. Activated by [Ph 3 C]-[B(C 6 F 5 ) 4 ], all of these iminoamido rare earth metal dialkyl complexes are active for living polymerization of isoprene, with activity and selectivity being sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 171 publications
2
37
1
Order By: Relevance
“…17,[35][36][43][44][45][46][47][48][49][50] On the other hand, reports of structurally characterized alkyl or aryl rare earth complexes bearing an imine functionality in the backbone are rare, [51][52] the majority being represented by phosphinimine ligands. [53][54][55][56][57][58][59][60] In our lab, the synthesis of an electrophilic metal alkyl complex supported by a Schiff base ferrocene ligand would continually fail. Although a few examples of alkyl yttrium complexes supported by a ligand containing an imine group exist, 53,61 in general, attempts to isolate such complexes resulted in the migration of the alkyl ligand to the imine group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,[35][36][43][44][45][46][47][48][49][50] On the other hand, reports of structurally characterized alkyl or aryl rare earth complexes bearing an imine functionality in the backbone are rare, [51][52] the majority being represented by phosphinimine ligands. [53][54][55][56][57][58][59][60] In our lab, the synthesis of an electrophilic metal alkyl complex supported by a Schiff base ferrocene ligand would continually fail. Although a few examples of alkyl yttrium complexes supported by a ligand containing an imine group exist, 53,61 in general, attempts to isolate such complexes resulted in the migration of the alkyl ligand to the imine group.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few examples of alkyl yttrium complexes supported by a ligand containing an imine group exist, 53,61 in general, attempts to isolate such complexes resulted in the migration of the alkyl ligand to the imine group. 57,[62][63] We and others [64][65] have reasoned that replacing the imine with a phosphinimine backbone would increase the robustness of the resulting yttrium alkyl complexes. Herein, we report the synthesis, characterization, and reactivity of two yttrium alkyls supported by a ferrocene-based diphosphinimine ligand.…”
Section: Introductionmentioning
confidence: 99%
“…The one‐pot acid–base reactions between the rare earth metal trialkyl complexes Ln(CH 2 SiMe 3 ) 3 (THF) 2 (Ln = Sc, Lu, and Y) and 1 equiv. of substituted α‐diimine ligands 2,6‐R 2 C 6 H 3 N = CH – CH = NC 6 H 3 R 2 ‐2,6 (R = i ‐Pr, Me) in toluene at room temperature gave straightforwardly the monoanionic iminoamido rare earth metal dialkyl complexes [2,6‐R 2 C 6 H 3 NCH 2 C(CH 2 SiMe 3 )=NC 6 H 3 R 2 ‐2,6]Ln(CH 2 Si Me 3 ) 2 (THF) 5a–5f ( 5a : Ln = Sc, R = i‐ Pr; 5b : Ln = Lu, R = i‐ Pr; 5c : Ln = Y, R = i‐ Pr; 5d : Ln = Sc, R = Me; 5e : Ln = Lu, R = Me; 5f : Ln = Y, R = Me) in high yields . All complexes 5a–5f are soluble in common organic solvents such as THF, toluene, and hexane [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, we reported that the cationic rare earth metal alkyl species generated by the monoanionic iminoamido dialkyl complexes 5a–5f and [Ph 3 C][B(C 6 F 5 ) 4 ] and Al i ‐Bu 3 could promote the living 3,4‐polymerization of isoprene to afford the mainly 3,4‐poly(IP) (3,4‐selectivity: 48–99%) with narrow molecular weight distribution [Fig. (b)] . The structure–reactivity relationship was observed in the isoprene polymerization catalyzed by these cationic iminoamido rare earth metal alkyl catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al. reported the one‐pot synthesis of a new class of monoanionic dialkyl rare‐earth metal complexes 122 and 123 bearing iminoamido ligands . Activated by [Ph 3 C][B(C 6 F 5 ) 4 ], all of these complexes showed high catalytic activities for living polymerization of IP with narrow molecular weight distributions.…”
Section: Stereoselective Polymerization Of Conjugated Dienesmentioning
confidence: 99%